2017
DOI: 10.1002/ece3.3099
|View full text |Cite
|
Sign up to set email alerts
|

Timing and pattern of annual silver eel migration in two European watersheds are determined by similar cues

Abstract: Many animals perform long‐distance migrations in order to maximize lifetime reproductive success. The European eel migrates several thousand kilometers between their feeding habitats in continental waters (fresh‐, brackish, and sea water) and their spawning area in the Sargasso Sea. Eels residing in freshwaters usually initiate their spawning migration as silver eels during autumn, triggered by diverse environmental cues. We analyzed the time series of silver eel downstream migration in Burrishoole, Ireland (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 40 publications
3
42
0
Order By: Relevance
“…Eels using the spillway gate passed the power station at a faster speed than those using other routes, which indicates that eels can be motivated or reluctant to pass barriers dependent on the physical and environmental conditions, as pointed out by Piper et al (). The eels seemed stimulated to migrate during floods, as also shown in other studies (Durif, Elie, Gosset, Rives, & Travade, ; Marohn et al, ; Sandlund et al, ; Trancart et al, ). However, there was large individual variation in migration timing, and some individuals spent a much longer time than the others to pass.…”
Section: Discussionsupporting
confidence: 79%
“…Eels using the spillway gate passed the power station at a faster speed than those using other routes, which indicates that eels can be motivated or reluctant to pass barriers dependent on the physical and environmental conditions, as pointed out by Piper et al (). The eels seemed stimulated to migrate during floods, as also shown in other studies (Durif, Elie, Gosset, Rives, & Travade, ; Marohn et al, ; Sandlund et al, ; Trancart et al, ). However, there was large individual variation in migration timing, and some individuals spent a much longer time than the others to pass.…”
Section: Discussionsupporting
confidence: 79%
“…Will the effect of increased density be increased mortality, due to more competition for resources or more predation from older eels, or reduced growth due to displacement to lower quality habitats? At very low densities, other effects like Allee effects, depensatory mechanisms, changing sex ratios or life‐history strategies can also obscure the relationship (see references in Poole et al, 2018; Sandlund et al, 2017). One should also note that developing river‐wise stock‐recruitment models for European eel is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…At some of the monitoring stations, like in the river Imsa, Norway, both upstream ascending elvers and downstream migrating silver eels are trapped and counted (Sandlund et al, 2017). The Imsa reference time series was started in the 1970s, and the age distribution and the population dynamics in this catchment were especially studied in the 1980s and 1990s, yielding fundamental knowledge on the ecology of European eels (Vøllestad & Jonsson, 1986, 1988; Vøllestad, Jonsson, Hvidsten, & Næsje, 1994; Vøllestad et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the importance of environmental variables may change over time and space, further complicating the understanding of their relative impacts. Recent findings (Sandlund et al, 2017) concluded that the onset of migratory behaviour in two catchments from northwest Europe is triggered by the same environmental variables. However, there is no evidence that the variables implicated in this migration are the same in the southern part of the eel's range, especially due to differences in climate between regions and to the prevalence of females in most studies.…”
mentioning
confidence: 99%